Electronic Portals of Executive Bodies of the State Power of the Subjects of the Russian Federation as Communicative Tool: The Empirical Research Results - S. A. Shtrikov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
The purpose of the article is to substantiate the directions of improving the communication potential of electronic portals of public authorities of the Russian Federation through an empirical analysis of their main problems and specific characteristics. The methodological basis of the paper is the focus group research with the participation of key stakeholders of the communication tools of regional authorities responsible for the development of industry. The study was attended by representatives of the authorities of the constituent entities of the Russian Federation responsible for interaction with industrial enterprises, representatives of industrial enterprises themselves, as well as representatives of research institutions or universities that are engaged in development for industry. The scenario of each focus group included both an assessment of the websites of the authorities responsible for the implementation of the industrial policy in the region and, in general, a description of the communication policy of the public authorities, which was based on the experience of respondents (stakeholders). The results of the analysis made it possible to rank the official portals of public authorities responsible for industrial development. The study concludes that the main barriers to the development of information society communication policies include: technological and infrastructural problems; the use of non-working or outdated communication tools, in particular, the lack of communication with social media accounts; the lack of visual and contextual content that emphasizes the specifics of the region; excessive politicization of the site; the information reporting nature of the site and the use of an exclusively bureaucratic language. These problems are systemic in nature and reflect the general problems of the communication policy of the public authorities of the constituent entities of the Russian Federation, as a result of which the organization of interaction with key stakeholders is not based on common ideas, objectives and meanings, but on disparate interests. Interaction of public authorities with key stakeholders within the framework of the government portal can be improved by working with the competence potential of public authorities; technological development of communication tools of public authorities, including the assessment of their effectiveness; formation of growth points and directions of transformation of communication policy in the context of the development of the information society.